2019
DOI: 10.3354/meps13086
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of functional diversity and composition in marine benthic ciliates along the coast of China

Abstract: Large-scale patterns of community composition and diversity along environmental gradients have been well studied for macroorganisms. However, the biogeography of microorganisms, especially ciliated protozoa, remains understudied. Here, we analyzed a comprehensive database of marine benthic ciliates found along the coast of China from 1991 to 2018 to examine the geographical patterns in species and trait composition and functional diversity. According to redundancy analysis conducted at large spatial scales, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 65 publications
2
12
0
1
Order By: Relevance
“…Among the habitat type groupings, the composition patterns also exhibited notable variations in our study especially for feeding habit trait (Figure 3). It is widely accepted that the variation of feeding habit composition can be attributed to the responses of ciliate communities to environmental and spatial changes in marine water (Xu et al, 2018, Xu andSoininen, 2019). In our study, for example, the proportion of bacterivores in mangroves is higher than other habitats, which was apparently correlated with the higher bacteria production due to the sufficient accumulation of organic detritus in mangroves compared with other habitats.…”
Section: Distribution Variations Of Ciliates Among the Subareas In Intertidal Neritic And Oceanic Areassupporting
confidence: 43%
See 2 more Smart Citations
“…Among the habitat type groupings, the composition patterns also exhibited notable variations in our study especially for feeding habit trait (Figure 3). It is widely accepted that the variation of feeding habit composition can be attributed to the responses of ciliate communities to environmental and spatial changes in marine water (Xu et al, 2018, Xu andSoininen, 2019). In our study, for example, the proportion of bacterivores in mangroves is higher than other habitats, which was apparently correlated with the higher bacteria production due to the sufficient accumulation of organic detritus in mangroves compared with other habitats.…”
Section: Distribution Variations Of Ciliates Among the Subareas In Intertidal Neritic And Oceanic Areassupporting
confidence: 43%
“…The ANOSIM analyses showed that the community variations of ciliates among the intertidal, neritic, and oceanic areas can be clearly distinguished for all taxonomic, motility, and feeding habit compositions. Similarly, both species and trait compositions showed spatial variations of benthic ciliates along the coast of China (Xu and Soininen, 2019). These suggest that taxonomic and ecological traits can give the same result in exploring the geographical patterns of ciliates on a large scale.…”
Section: Comparison Of Distributions Of Ciliatementioning
confidence: 66%
See 1 more Smart Citation
“…Five traits, sub-divided into 13 categories, were selected according to Xu & Soininen (2019). The traits reflect morphological characteristics (body size, degree of flexibility, and body form) and behavior (feeding and mobility) ( Table S1 in the Supplement at www.…”
Section: Ciliate Identification and Trait Analysismentioning
confidence: 99%
“…investigaram se as propriedades do solo durante a secagem de áreas alagadas ("wetlands") são influenciadas pelas características funcionais das plantas que compõem a vegetação e comprovaram2.3.2 Diversidade funcional em estudos com CiliophoraDe acordo com Weisse (2017) a pesquisa sobre diversidade funcional aplicada aos ciliados ainda está nos seus primórdios, pois são necessárias muitas informações para estabelecer os traços para estes organismos que ainda são desconhecidos. Estudos foram realizados em diferentes ecossistemas, como no solo por Coûteaux & Darbyshire (1998), em águas costeiras(XU, H. et al, 2016;ZHAO et al, 2016;ZHONG et al, 2017;AL et al, 2018a;XU, G. et al, 2018b;XU & SOININEN, 2019;ZHONG et al, 2019;GUI et al, 2020;GUO et al, 2020), em áreas alagadas "wetlands"XU, Y. et al, 2018b;LIU et al, 2019;composição funcional da comunidade de protistas ciliados,Xu, H. et al (2016) utilizaram a abordagem funcional espacialmente para viabilizar o uso de traços funcionais para a comunidade de ciliados na bioavaliação da qualidade da água em ambientes marinhos Al et al (2018b). assumindo que a disponibilidade de alimento é diferente ao longo da coluna d'água, funcionais(XU, Y. et al 2018b).…”
unclassified